2016
DOI: 10.1002/ajhb.22933
|View full text |Cite
|
Sign up to set email alerts
|

The allele frequency of ALDH2*Glu504Lys and ADH1B*Arg47His for the Ryukyu islanders and their history of expansion among East Asians

Abstract: Our data suggest that the derived allele of ALDH2 came with the Yayoi immigrants from the Asian continent to the Japanese archipelago. However, the derived allele of ADH1B is unlikely to be related to the Yayoi migration. Therefore, we postulate that the expansion of the derived allele of ADHIB in East Asia could be traced back to the last glacial period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…The top SNPs from the SDS analysis in ADH cluster and BRAP-ALDH2 are in linkage disequilibrium (LD) with functional missense SNPs of ADH1B (Arg47His, rs1229984) and ALDH2 (Glu504Lys, rs671) ( r 2 = 0.76 and 0.86 in the WGS dataset 1, respectively). These SNPs mediate differences in alcohol metabolism by altering the enzymatic activities of alcohol dehydrogenase and aldehyde dehydrogenase, and have been suggested in evolutional adaptations of global populations including Asians mostly by candidate gene-based approaches 22 . Our genome-wide analysis initially indicates that both of these alcohol metabolism-related SNPs are under the strongest recent natural selection pressure in the Japanese population.…”
Section: Resultsmentioning
confidence: 99%
“…The top SNPs from the SDS analysis in ADH cluster and BRAP-ALDH2 are in linkage disequilibrium (LD) with functional missense SNPs of ADH1B (Arg47His, rs1229984) and ALDH2 (Glu504Lys, rs671) ( r 2 = 0.76 and 0.86 in the WGS dataset 1, respectively). These SNPs mediate differences in alcohol metabolism by altering the enzymatic activities of alcohol dehydrogenase and aldehyde dehydrogenase, and have been suggested in evolutional adaptations of global populations including Asians mostly by candidate gene-based approaches 22 . Our genome-wide analysis initially indicates that both of these alcohol metabolism-related SNPs are under the strongest recent natural selection pressure in the Japanese population.…”
Section: Resultsmentioning
confidence: 99%
“…Other physiological and morphological traits of Jomon people unidentified from skeletal remains, e.g. alcohol tolerance (Koganebuchi et al, 2017), Rh-blood type, and ear wax (Omoto, 1992), have been inferred indirectly from the geographical distribution of variants in the Japanese archipelago. Recent ancient DNA studies also uncovered phenotypic traits of Jomons, such as ear-wax and ABO blood type (Sato et al, 2009b(Sato et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The LDproxy analyses indicated that rs671 in ALDH2 and five SNPs, including three disease‐associated SNPs detected by our longitudinal exome‐wide association studies, were in significant LD ( r 2 > 0.8) in JPT from the 1KGP (Table ). Recent positive selection is likely to have acted on the genomic region containing rs671, and the minor alleles have expanded throughout East Asia in recent evolutionary time (Koganebuchi et al, ; Luo et al, ; Oota et al, ; Yasukochi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the function prediction tools suggest that the missense variant has an effect on the protein function (PolyPhen score = 0.964, SIFT = 0.019, CADD scaled C‐score = 34.0, and PhyloP = 9.71). It is possible that the derived allele of rs671 may have arisen ~8,000 years ago when large‐scale rice cultivation started in southern China (Koganebuchi et al, ). Previous studies suggested that positive selection has acted on ALDH2 in EAS because of acquired resistance against parasite infection related to large‐scale rice cultivation (Koganebuchi et al, ; Luo et al, ; Oota et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation